The epidemiology and severity of respiratory viral infections in a tropical country: Ecuador, 2009-2016 - Saverio Caini; Doménica de Mora; Maritza Olmedo; Denisses Portugal; María A. Becerra; Marcela Mejía; María C. Pacurucu; Jenny Ojeda; Guglielmo Bonaccorsi; Chiara Lorini; John Paget; Alfredo Bruno (Elsevier, 2019)
Background: Respiratory viral infections (RVI) are a leading cause of mortality worldwide. We compared the epidemiology and severity of RVI in Ecuador during 2009-2016. Methods: Respiratory specimens collected within the national surveillance system were tested for influenza viruses, respiratory syncytial virus (RSV), adenovirus, parainfluenza virus, and human metapneumovirus. Overall and virus-specific positive detection rate (PDR) were calculated and compared the timing of epidemics caused by the different viruses. Logistic regression models were used to compare the age distribution and risk of death across respiratory viruses. Results: A total of 41,172 specimens were analyzed: influenza (PDR = 14.3%) and respiratory syncytial virus (RSV) (PDR = 9.5%) were the most frequently detected viruses. Influenza epidemics typically peaked in December-January and RSV epidemics in March; seasonality was less evident for the other viruses. Compared to adults, children were more frequently infected with RSV, adenovirus, parainfluenza, and influenza B, while the elderly were less frequently infected with influenza A(H1N1)p. The age-adjusted risk of death was highest for A(H1N1)p (odds ratio [OR] 1.73, 95% confidence intervals [CI] 1.38-2.17), and lowest for RSV (OR 0.75, 95%CI 0.57-0.98). Conclusions: Whilst influenza and RSV were the most frequently detected pathogens, the risk of death differed by RVI, being highest for pandemic influenza and lowest for RSV. Keywords: Respiratory viral infections, Epidemiology, Age distribution, Case-fatality ratio, Ecuador